Perbandingan Ketepatan Formula Risanto dan Johnson Toshack dalam Menentukan Taksiran Berat Janin - Netti Herawati; Herinawati Herinawati; Ajeng Galuh Wuryandari; Ry Eny Mian Marisi Simanjuntak; Miftahul Jannah (Universitas Baiturrahim, 2022)
Measurement of uterine fundal height (TFU) to determine the estimated fetal weight (TBJ) is an important component of antenatal care in labor management. Babies born with low body weight or born with very large body weight are associated with increased complications during labor and the puerperium. This study aims to compare the accuracy of the Risanto and Johnson Toshack formulas in determining the estimated fetal weight. The design of this study was cross-sectional, with the sample being parturient mothers in the PMB working area of the Tangkit Health Center in 2022 who met the inclusion criteria, which amounted to 87 people. The sampling technique is accidental sampling. The results showed that the Risanto and Johnson Toshack formulas were compatible in estimating the baby's birth weight (p-value 0.497 and 0.377). The average difference between the TBJ of Risanto's theory and the baby's weight is 34.42 grams, while the average difference between the TBJ of Johnson Toshack's formula is 171.15 grams. The test results comparing the accuracy of the Risanto formula and the Johnson Toshack formula, the average value of TBJ Johnson Toshack is greater than the average value of TBJ Risanto, and TBJ Risanto is closer to the baby's birth weight. The conclusion of this study shows that Risanto's TBJ measurement is more accurate than Johnson's TBJ Toshack. Measurement TBJ uses the Risanto formula that health workers can apply to detect fetal well-being, including estimated fetal weight during pregnancy and delivery.